2000
DOI: 10.1074/jbc.275.9.6411
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of the Src Homology 2 Domains of Phospholipase C-γ1 (PLC-γ1) in Platelet-derived Growth Factor-induced Activation of PLC-γ1 in Intact Cells

Abstract: Upon stimulation of cells with platelet-derived growth factor (PDGF), phospholipase C-␥1 (PLC-␥1) binds to the tyrosine-phosphorylated PDGF receptor through one or both of its Src homology 2 (SH2) domains, is phosphorylated by the receptor kinase, and is thereby activated to hydrolyze phosphatidylinositol 4,5-bisphosphate. Association of PLC-␥1 with the insoluble subcellular fraction is also enhanced in PDGF-stimulated cells. The individual roles of the two SH2 domains of PLC-␥1 in mediating the interaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 39 publications
4
21
0
Order By: Relevance
“…However, the SH2N domain but not the SH2C domain interacted with these adapter proteins in intact cells (6,33). The isolated PLC-␥1 SH2C domain was also shown by nuclear magnetic resonance to bind a phosphorylated peptide encompassing tyrosine 1021 of the platelet-derived growth factor (PDGF) receptor, but a role for this interaction in PDGF-activated cells was not identified (15,25). Taken together, these studies suggest that access to the SH2C domain is tightly regulated by the overall structure of PLC-␥1.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…However, the SH2N domain but not the SH2C domain interacted with these adapter proteins in intact cells (6,33). The isolated PLC-␥1 SH2C domain was also shown by nuclear magnetic resonance to bind a phosphorylated peptide encompassing tyrosine 1021 of the platelet-derived growth factor (PDGF) receptor, but a role for this interaction in PDGF-activated cells was not identified (15,25). Taken together, these studies suggest that access to the SH2C domain is tightly regulated by the overall structure of PLC-␥1.…”
mentioning
confidence: 53%
“…This area is composed of two Src homology 2 (SH2) domains and an Src homology 3 (SH3) domain. The N-terminal SH2 domain (SH2N) is critical for binding to either tyrosine-phosphorylated receptor kinases or adaptor molecules that mediate PLC-␥1 relocation to the plasma membrane (6,14,25). The function of the C-terminal SH2 domain (SH2C) is less clear but is also essential for PLC-␥1 activation (1,6,14,33).…”
mentioning
confidence: 99%
“…In contrast to the EGF receptor-signaling, there is one specific autophosphorylated tyrosine that specifies an association with the PLC-γ1 SH2 domains for platelet-derived growth factor (PDGF), fibroblast growth factor (FGF), and nerve growth factor (NGF) receptors (for example, the Tyr1021 of the β-type PDGF receptor) (Valius et al, 1993). Both SH2 domains of PLC-γ1 have been shown to be required for growth factor-induced receptor association and Ca 2+ mobilization and also for association with the EGF receptor (Chattopadyay et al, 1999;Poulin et al, 2000). The N-terminal SH2 domain of PLC-γ1 is known to play a major role in the association with the activated growth factor receptor, while the C-terminal SH2 domain is considered to play a minor role (Chattopadyay et al, 1999;Poulin et al, 2000).…”
Section: Activation Of Plc-γ γ γ γ1mentioning
confidence: 99%
“…Both SH2 domains of PLC-γ1 have been shown to be required for growth factor-induced receptor association and Ca 2+ mobilization and also for association with the EGF receptor (Chattopadyay et al, 1999;Poulin et al, 2000). The N-terminal SH2 domain of PLC-γ1 is known to play a major role in the association with the activated growth factor receptor, while the C-terminal SH2 domain is considered to play a minor role (Chattopadyay et al, 1999;Poulin et al, 2000). However, recently, it has been reported that the C-terminal SH2 domain of PLC-γ1 is involved in interactions with synaptojanin (Ahn et al, 1998), the actin-cytoskeleton (Pei et al, 1996), PIP 3 (Bae et al, 1998;Rameh et al, 1998) and FAK (Zhang et al, 1999).…”
Section: Activation Of Plc-γ γ γ γ1mentioning
confidence: 99%
See 1 more Smart Citation